HUBUNGAN HARGA DIRI DAN KEPERCAYAAN DIRI REMAJA PANTI ASUHAN AISYIYAH DI SIDOARJO - Annisa Hapsari Martha; Ramon Ananda Paryontri (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Some adolescents who live in orphanages have a lack of self-confidence. This study aims to find the relationship between self-esteem and self-confidence in adolescents in orphanages in Sidoarjo. The method used is a quantitative method with a correlational quantitative approach. The population for this study was 271 students, who ranged in age from 13 to 17 years. The research was conducted at Aisyiyah Orphanage throughout Sidoarjo, YPM Mabarrot Orphanage, and Ar-Rahman Ar-Rahim Orphanage. In this study, saturated sampling was used as a sampling technique. The total sample used by researchers was 271 samples with saturated sampling as a sampling technique, where all members of the population were used as samples. Data analysis in this study used Spearmen’s rho correlation with the help of JASP 0.16.2.0 software. It was found that the correlation result of Spearman's rho = 0.413 (p < 0.001), this shows that the hypothesis is accepted, meaning that there is a positive relationship between self-confidence and self-esteem. This is in accordance with various studies on self-esteem, which is one of the factors that influence the development of self-confidence.